2003
DOI: 10.1073/pnas.2133733100
|View full text |Cite
|
Sign up to set email alerts
|

Damped elastic recoil of the titin spring in myofibrils of human myocardium

Abstract: The giant protein titin functions as a molecular spring in muscle and is responsible for most of the passive tension of myocardium. Because the titin spring is extended during diastolic stretch, it will recoil elastically during systole and potentially may influence the overall shortening behavior of cardiac muscle. Here, titin elastic recoil was quantified in single human heart myofibrils by using a high-speed charge-coupled device-line camera and a nanonewtonrange force sensor. Application of a slack-test pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 40 publications
3
72
0
4
Order By: Relevance
“…It has been shown earlier that the unloaded shortening of striated muscle is influenced by viscous and viscoelastic forces (de Tombe and ter Keurs, 1990;de Tombe and ter Keurs, 1991;de Tombe and ter Keurs, 1992). It has even been suggested that titin might play a role in influencing unloaded shortening velocity (Kulke et al, 2001;Opitz et al, 2003). We suggest a possible mechanism of how titin might inhibit unloaded sarcomere shortening (Fig.…”
Section: Binding Of F-actin and Thin Filaments By Pevk Segments And Fmentioning
confidence: 52%
“…It has been shown earlier that the unloaded shortening of striated muscle is influenced by viscous and viscoelastic forces (de Tombe and ter Keurs, 1990;de Tombe and ter Keurs, 1991;de Tombe and ter Keurs, 1992). It has even been suggested that titin might play a role in influencing unloaded shortening velocity (Kulke et al, 2001;Opitz et al, 2003). We suggest a possible mechanism of how titin might inhibit unloaded sarcomere shortening (Fig.…”
Section: Binding Of F-actin and Thin Filaments By Pevk Segments And Fmentioning
confidence: 52%
“…The driving force for LV filling is primarily the elastic recoil caused by the "springs" available in the form of the protein titin (13) in the contracting actin-myosin complex and elastic structures in the extracellular matrix (12,30). The LV has a higher muscle mass compared with the RV and thereby contains more titin and a larger possibility for elastic recoil.…”
Section: Mechanisms Explaining Interventricular Differences and Similmentioning
confidence: 99%
“…Different titin isoforms have also been used to explain differences in passive stiffness between psoas and soleus rabbit fibers (10,22). Furthermore, degradation or extraction of titin from myofibrils leads to a rapid drop in passive force (12,26,35) in cardiac and skeletal myofibrils.…”
mentioning
confidence: 99%